2009
DOI: 10.5194/bg-6-2985-2009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal responses of coastal hypoxia to nutrient loading and physical controls

Abstract: Abstract. The incidence and intensity of hypoxic waters in coastal aquatic ecosystems has been expanding in recent decades coincident with eutrophication of the coastal zone. Worldwide, there is strong interest in reducing the size and duration of hypoxia in coastal waters, because hypoxia causes negative effects for many organisms and ecosystem processes. Although strategies to reduce hypoxia by decreasing nutrient loading are predicated on the assumption that this action would reverse eutrophication, recent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
265
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(279 citation statements)
references
References 169 publications
5
265
0
2
Order By: Relevance
“…Mesoscale intrusions of subsurface suboxic waters from the Rim Current of the Black Sea general circulation system also episodically modulate the near-bottom oxygen structure of northwestern shelf (Black Sea Commission, 2008). Longterm observations show that coastal hypoxia off large river mouths and in estuaries/bays has an important seasonal (Rabalais et al, 2001) and/or inter-annual component (Gilbert et al, 2005;Kemp et al, 2009) that can be related to climate variability as well. For example, the annual discharge of the Mississippi River is predicted to increase by 20% if the concentration of atmospheric CO 2 doubles, and nutrient load would increase as well, which will induce stronger stratification and more serious eutrophication, followed by an ever intensified hypoxia on the Louisiana Continental Shelf (Rabalais and ).…”
Section: Hypoxia Off River Mouths and In Estuariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoscale intrusions of subsurface suboxic waters from the Rim Current of the Black Sea general circulation system also episodically modulate the near-bottom oxygen structure of northwestern shelf (Black Sea Commission, 2008). Longterm observations show that coastal hypoxia off large river mouths and in estuaries/bays has an important seasonal (Rabalais et al, 2001) and/or inter-annual component (Gilbert et al, 2005;Kemp et al, 2009) that can be related to climate variability as well. For example, the annual discharge of the Mississippi River is predicted to increase by 20% if the concentration of atmospheric CO 2 doubles, and nutrient load would increase as well, which will induce stronger stratification and more serious eutrophication, followed by an ever intensified hypoxia on the Louisiana Continental Shelf (Rabalais and ).…”
Section: Hypoxia Off River Mouths and In Estuariesmentioning
confidence: 99%
“…Comparative studies also clarify how biogeochemical dynamics defines the magnitude and consequences of coastal hypoxia. High-resolution measurements have enabled the establishment of cross-boundary and mechanistic understanding of the emergent, evolving and declining phases of coastal hypoxia (Kemp et al, 2009). The episodic, periodic (i.e.…”
Section: Understanding the Causes Of Coastal Hypoxiamentioning
confidence: 99%
“…Inflow of nutrients, especially nitrogen (N), stimulates primary production in the estuary, occasionally leading to a rise in frequency and intensity of harmful algal blooms (Weise et al 2002;Bricker et al 2008) which induce massive mortality of marine fish, birds and mammals . Organic carbon exported from the watershed and plankton produced within the estuary eventually sediments into deep estuarine waters, where enhanced microbial activity induces hypoxia and anoxia (Kemp et al 2009). Median rates of oxygen decline are more severe in a 30 km band near the coast than in the open ocean ([100 km from the coast) (Gilbert et al 2010) which also exerts a range of negative effects on marine coastal ecosystems (Diaz and Rosenberg 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia occurs naturally in many coastal environments with restricted circulation, such as fjords and inland seas, but hypoxia in locations with less restricted circulation both offshore (e.g., California Current, Benguela Current) and near-shore (Diaz and Rosenberg, 2008;Gilbert et al, 2010) is increasingly being reported. This may reflect changes in ocean circulation (Gilbert et al, 2005) or increased eutrophication (Kemp et al, 2009). Shallow or seasonally stratified water columns can be ventilated by vertical mixing events, which may prevent hypoxia from becoming persistent (Rabalais et al, 2001).…”
mentioning
confidence: 99%